"BRILLIANT STUDENTS, FASCINATING SCHOOL": AN EXPERIENCE REPORT ON PARTICIPATORY MANAGEMENT AND STUDENT PROTAGONISM IN ELEMENTARY SCHOOL - de Aguiar Costa, Julimar (Revista Gênero e Interdisciplinaridade, 2026)
This article presents an experience report on the implementation of the project “Brilliant Students, Fascinating School”, developed in a public elementary school in the municipality of Tianguá-CE. The project proposed a model of participatory classroom management, based on the recognition of students’ talents, co-responsibility and the construction of a living and affective curriculum. The experience was implemented in a 7th grade class and compared to a control class. The article describes the project’s genesis, its nine implementation stages, the classroom organizational structure (Organization, Human Relations, Marketing, Monitoring and Evaluation sectors), management routines (daily reports, weekly and monthly meetings) and formative assessment instruments. The observed results indicate greater engagement, development of oral communication, reduction of delays in homework submission and discovery of previously hidden talents. This report is intended for teachers and managers interested in innovative participatory management practices.